GE_GERICHTE C/30917/2010 vom 22. November 2013 - GE Cour de justice (2013)
; DIVORCE ; MESURE PROVISIONNELLE ; OBLIGATION D'ENTRETIEN ; CONGÉ NON PAYÉ ; REVENU HYPOTHÉTIQUE ; FORTUNE | CC.125; CC.285.al.1